Policy proposals to promote inclusion of caregivers in the research funding system - Torres, Isabel L.; Collins, Rayven-Nikkita; Hertz, Anaelle; Liukkonen, Martta (Frontiers in Education, 2024)
Research funding is critical for scientific production and career advancement in science, technology, engineering, mathematics, and medicine (STEMM). The COVID-19 pandemic has unmasked a deeply flawed research funding system riddled by inequitable policies, biased evaluations, and a lack of transparency and accountability. While most scientists were affected by the pandemic to some extent, evidence shows that women with caregiving responsibilities were disproportionately impacted, with long-term effects on their careers. However, despite calls for change by scientists globally, whose careers depend largely on funding success, decision-makers have made little to no effort to reform a funding system that marginalises a large proportion of researchers, including women, and especially mothers. Here, we review the current literature on gender bias in the STEMM funding process and propose a set of specific, actionable policies to promote caregiver inclusion and close the gender gap in research funding.